The shortage of seafarers : developing industry/employer of choice and employment brand strategies - Sofian, Norsofiana. (2010)
The globally recognized BIMCO/ISF study on the Demand and Supply of seafarers has been reporting the shortage of seafarers at an interval of every 5 years since 1990. The shortage has been a persisting issue and affects every maritime nation. Over the years, nations are fast developing and there are many other job opportunities available on shore instead. With many other factors included, the seafaring industry is slowly losing its luster and attractiveness.